2015
DOI: 10.3897/bdj.3.e5085
|View full text |Cite
|
Sign up to set email alerts
|

Bumble Bees (Hymenoptera: Apidae: Bombus spp.) of Interior Alaska: Species Composition, Distribution, Seasonal Biology, and Parasites

Abstract: BackgroundDespite the ecological and agricultural significance of bumble bees in Alaska, very little is known and published about this important group at the regional level. The objectives of this study were to provide baseline data on species composition, distribution, seasonal biology, and parasites of the genus Bombus at three major agricultural locations within Alaska: Fairbanks, Delta Junction, and Palmer, to lay the groundwork for future research on bumble bee pollination in Alaska.New informationA total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Studies have consistently demonstrated blue vane traps to be highly effective at sampling large insects, particularly bumble bees, though additional sampling methods may be required to capture a complete picture of bee communities (Stephen and Rao 2005, 2007; Rao and Stephen 2007; Wilson et al 2008; Geroff et al 2014; Buchanan et al 2017; Gibbs et al 2017; McCravy and Ruholl 2017; Rhoades et al 2017). Studies have also shown blue vane traps to be effective at passively sampling the species concerned in this study, including B. fervidus, B. flavidus, B. insularis , B. occidentalis , and B. suckleyi (Kimoto et al 2012, Pampell et al 2015, Rhoades et al 2016, Gibbs et al 2017, Rivers et al 2018). Nevertheless, additional targeted sampling efforts may be necessary to conclusively establish this case of bumble bee extirpation.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Studies have consistently demonstrated blue vane traps to be highly effective at sampling large insects, particularly bumble bees, though additional sampling methods may be required to capture a complete picture of bee communities (Stephen and Rao 2005, 2007; Rao and Stephen 2007; Wilson et al 2008; Geroff et al 2014; Buchanan et al 2017; Gibbs et al 2017; McCravy and Ruholl 2017; Rhoades et al 2017). Studies have also shown blue vane traps to be effective at passively sampling the species concerned in this study, including B. fervidus, B. flavidus, B. insularis , B. occidentalis , and B. suckleyi (Kimoto et al 2012, Pampell et al 2015, Rhoades et al 2016, Gibbs et al 2017, Rivers et al 2018). Nevertheless, additional targeted sampling efforts may be necessary to conclusively establish this case of bumble bee extirpation.…”
Section: Discussionmentioning
confidence: 79%
“…Our sampling focused on a diverse range of habitats representative of the island landscape (e.g., woodlands, wetlands, clearcuts, rural areas, and gardens, all within a forested matrix), including areas in the vicinity of historical collection sites (Figure 1). Studies have consistently demonstrated blue vane traps to be highly effective at sampling large insects, particularly bumble bees, though additional sampling methods may be required to capture a complete picture of bee communities Rao 2005, 2007 (Kimoto et al 2012, Pampell et al 2015, Rhoades et al 2016, Rivers et al 2018. Nevertheless, additional targeted sampling efforts may be necessary to conclusively establish this case of bumble bee extirpation.…”
Section: Extirpation: the Case Of Galiano Island's Missing Bumble Beesmentioning
confidence: 99%
“…Concern is also mounting regarding the fate of the cuckoo bumblebees, which not only depend on them but face these same anthropogenic threats. A number of publications have noted the rarity, absence, or decline of cuckoo bumblebees which had previously been recorded (e.g., Colla et al, 2012; Figueroa & Bergey, 2015; Grixti et al, 2009; Pampell et al, 2015; Richardson et al, 2018 in North America; and Kolosova et al, 2016; Kosior et al, 2007; Rasmussen et al, 2022 in Europe)—drawing attention to the need to monitor and assess the status of Psithyrus populations through increased survey efforts. Understanding threats to cuckoo bumblebees and making assessments of their populations, however, requires more than just surveys of their abundance and distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Our sampling focused on a diverse range of habitats representative of the island landscape (e.g., woodlands, wetlands, clearcuts, rural areas, and gardens, all within a forested matrix), including areas in the vicinity of historical collection sites (Figure 1). Studies have consistently demonstrated blue vane traps to be highly effective at sampling large insects, particularly bumble bees, though additional sampling methods may be required to capture a complete picture of bee communities Rao 2005, 2007 (Kimoto et al 2012, Pampell et al 2015, Rhoades et al 2016, Rivers et al 2018. Nevertheless, additional targeted sampling efforts may be necessary to conclusively establish this case of bumble bee extirpation.…”
Section: Extirpation: the Case Of Galiano Island's Missing Bumble Beesmentioning
confidence: 99%